GAMBARAN TINGKAT PENGETAHUAN DAN KETERAMPILAN PEDAGANG TENTANG PERTOLONGAN PERTAMA PADA KEJADIAN ORANG TENGGELAM DI AREA WISATA PANTAI PANJANG KOTA BENGKULU - Fikrah Mardatillah Hasanah (Universitas Bengkulu, 2022)
In general, drowning can occur due to accidents, either directly or by certain factors. Drowning requires immediate treatment and assistance. Drowning is the third leading cause of death from accidental injury. This happened due to several factors, including the lack of knowledge of rescuers about first aid for drowning victims, lack of socialization about the benefits of first aid for drowning victims among the community, including traders. The purpose of this study was to describe the level of knowledge and skills of traders about first aid in the incident of drowning in the Pantai Panjang tourist area, Bengkulu City. This type of research uses descriptive observation method with a quantitative approach using snawball sampling technique. The results of this study obtained the level of knowledge of traders more than half (55%) in the good category and the skill level of traders (53%) in the good category. It is recommended that this study can be a reference to determine the importance of first aid in the event of a drowning person.